(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
In many African communities, cultural beliefs and practices significantly influence social dynamics and individual experiences. In Elele, a town in Rivers State, Nigeria, twin children often face unique socio-cultural limitations. This study explores these limitations and examines their implications for peaceful co-existence within the community. A qualitative research approach was adopted, involving in-depth interviews and focus group discussions with 50 participants, including parents of twins, community leaders, and the twins themselves. Data were collected over a six-month period from January to June 2024. Thematic analysis was used to identify and interpret patterns and themes related to the socio-cultural experiences of twin children. The findings reveal that twin children in Elele are subject to various socio-cultural limitations, including stigmatization, restricted social interactions, and exclusion from certain community activities. These limitations are rooted in traditional beliefs that view twins as omens or bearers of misfortune. The study also found that these socio-cultural practices contribute to social tension and conflict within the community, as families of twins often feel marginalized and discriminated against. The socio-cultural limitations imposed on twin children in Elele have significant implications for peaceful co-existence. Addressing these issues requires community-based interventions aimed at promoting cultural awareness, inclusivity, and acceptance. Educational programs and dialogue sessions involving community leaders and members can help to challenge and change harmful beliefs and practices, fostering a more harmonious and inclusive community.